Targeting the epithelial-mesenchymal transition (EMT) pathway with combination of Wnt inhibitor and chalcone complexes in lung cancer cells - Erturk, Elif; Onur, Omer E.; Aydin, Ipek; Akgun, Oguzhan; Coskun, Demet; Ari, Ferda (Wiley, 2023)
Non-small cell lung cancer (NSCLC) is the most common type of the lung cancer. Despite development in treatment options in NSCLC, the overall survival ratios is still poor due to epithelial and mesenchymal transition (EMT) feature and associated metastasis event. Thereby there is a need to develop strategy to increase antitumor response against the NSCLC cells by targeting EMT pathway with combination drugs. Niclosamide and chalcone complexes are both affect cancer cell signaling pathways and therefore inhibit the EMT pathway. In this study, it was aimed to increase antitumor response and suppress EMT pathway in NSCLC cells by combining niclosamide and chalcone complexes. SRB cell viability assay was performed to investigate the anticancer activity of drugs. The drugs were tested on both NSCLC cells (A549 and H1299) and normal lung bronchial cells (BEAS-2B). Then the two drugs were combined and their effects on cancer cells were evaluated. Fluorescence imaging and enzyme-linked immunosorbent assay were performed on treated cells to observe the cell death manner. Wound healing assay, real-time quantitative polymerase chain reaction, and western blot analysis were performed to measure EMT pathway activity. Our results showed that niclosamide and chalcone complexes combination kill cancer cells more than normal lung bronchial cells. Compared to single drug administration, the combination of both drugs killed NSCLC cells more effectively by increasing apoptotic activity. In addition, the combination of niclosamide and chalcone complexes decreased multidrug resistance and EMT activity by lowering their gene expressions and protein levels. These results showed that niclosamide and chalcone complexes combination could be a new drug combination for the treatment of NSCLC.
Keywords: chalcone complexes; drug resistance; epithelial-mesenchymal transition (EMT); niclosamide; NSCLC